2010
DOI: 10.1074/jbc.m110.115634
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Intracellular Domains as Key Determinants of the Quaternary Structure and Function of Receptor Heteromers

Abstract: It was inferred that different molecular mechanisms were involved in GPCR homo-and heteromerization. For family C GPCRs, disulfide bonds between extracellular domains as well as coiled-coil interactions between C-terminal domains seem to be necessary for the formation of functional homomeric or heteromeric receptors (8). For oligomerization of family A GPCRs, the helical transmembrane (TM) domains seem to be particularly important (7, 9 -15). In this study, by using mutated A 2A , CB 1 , and D 2 receptors, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 34 publications
4
84
0
2
Order By: Relevance
“…Therefore, CB 1 Rs have been shown previously to interact with other G protein-coupled receptors, including dopamine D 2 receptors (which promotes a switch in the preferential coupling from G i to G s ) (27), D 2 receptors and adenosine A 2A receptors simultaneously (producing a negative modulation of D 2 receptor function by A 2A and CB 1 R agonists) (28), opioid receptors (which produces a negative cross-talk between protomers) (29), orexin OX 1 receptors (eliciting a positive cross-talk in response to orexin and cross-antagonism) (30), and angiotensin AT 1 receptors (resulting in the potentiation of AT 1 receptor signaling) (31). More recently, coimmunoprecipitation assays in HEK293 cells have suggested that CB 1 R can form heteromers with GPR55 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CB 1 Rs have been shown previously to interact with other G protein-coupled receptors, including dopamine D 2 receptors (which promotes a switch in the preferential coupling from G i to G s ) (27), D 2 receptors and adenosine A 2A receptors simultaneously (producing a negative modulation of D 2 receptor function by A 2A and CB 1 R agonists) (28), opioid receptors (which produces a negative cross-talk between protomers) (29), orexin OX 1 receptors (eliciting a positive cross-talk in response to orexin and cross-antagonism) (30), and angiotensin AT 1 receptors (resulting in the potentiation of AT 1 receptor signaling) (31). More recently, coimmunoprecipitation assays in HEK293 cells have suggested that CB 1 R can form heteromers with GPR55 (32).…”
Section: Discussionmentioning
confidence: 99%
“…These include cooperative binding of certain ligands to adenosine A 2A and A 1 receptor heteromers (see below and Orru et al, 2011a). Furthermore, oligomerization of more than two different GPCRs has been suggested from studies with sequential BRET-FRET, BRET plus bimolecular fluorescence complementation (Carriba et al, 2008;Cabello et al, 2009;Navarro et al, 2010). Tentatively, these apparent heterotrimers could represent heteromultimers of homomers, as suggested for adenosine A 2A -dopamine D 2 -cannabinoid CB 1 receptor heteromers (Navarro et al, 2010).…”
Section: Determinants Of G Protein-coupled Receptor Heteromerizationmentioning
confidence: 99%
“…These electrostatic interactions depend on the very asymmetric and disordered structure of intracellular domains and have been suggested to be involved in several receptor heteromers (Ciruela et al, 2004;Woods and Ferré, 2005;Navarro et al, 2010;O'Dowd 2012O'Dowd , 2013. Several general features of the regions involved in these interactions have been outlined: one region, in one of the receptors, contains a series of adjacent arginine residues, and the other region, in the other receptor, contains acidic residues, with several adjacent residues or at least one phosphorylated serine.…”
Section: Determinants Of G Protein-coupled Receptor Heteromerizationmentioning
confidence: 99%
“…the number of component subunits) opening the possibility that oligomeric assemblies of different order could be formed (Agnati et al, 2010a). Navarro et al (2010) were among the first to advance evidence for the role of interaction interfaces between protomers in orchestrating the quaternary structure of heteromers. This study was focused on adenosine A 2A , dopamine D 2 , and cannabinoid CB 1 receptors.…”
Section: Quaternary Structure Of Gpcr Complexesmentioning
confidence: 99%